الدراسات السيميائية للقرآن الكريم - Ayad Abdullah; Mohammad Najib Jaffar; Nur Hamimi Zainuddin; Kirembwe Rashid Abdul Hamed; Lubna Abd Rahman; Adibah Sulaiman; Hishomudin Ahmad (Centre of Quranic Research (CQR), University of Malaya, 2024)
Volume: 8 No: 1